ENTREPRENEURSHIP AND INNOVATIONS FOR SUSTAINABLE DEVELOPMENT IN THE ERA OF DISRUPTION IN NIGERIA. (Journal of the Management Sciences, 2024)
The study focused on entrepreneurship innovation for sustainable development in the era of disruption in Nigeria. The objectives of this study are to analyze the challenges hindering entrepreneurship and Innovations for development in Nigeria; and to examine entrepreneurship and innovation as essential drivers of development in times of disruption in Nigeria. This a conceptual paper, anchored on the theory of diffusion of innovation propounded by Everett Roger, which describes the pattern of how new ideas or innovations spread throughout a society from a concentrated few user to a large general population of users across time as knowledge and use of the innovation builds. Findings showed that entrepreneurship and innovation are essential drivers for sustainable development, helping society adapt to disruptions while addressing environmental, social, and economic challenges. Entrepreneurship hold the potential to shape a more sustainable and resilient future for the global world. It was recommended that government should make policies that will favour small, medium and large-scale businesses in order to reduce unemployment rate and increase Gross Domestic Product.Government should also create conducive industrial environment by providing the rural and urban sectors with basic infrastructures such as industrial zones; affordable, steady and reliable electricity; water supply; education; health services; and security.
Keywords: Entrepreneurship, innovation, disruption, sustainability, Nigeria.